Development of cost-efficient UHPC with local materials in Colombia - Abellán García, Joaquín; Torres Castellanos, Nancy; Fernández Gómez, Jaime; Núñez López, Andrés (Books on Demand, 2020)
Ultra-high-performance concrete (UHPC) is an essential innovation in concrete research of recent decades. However, because of the high contents of cement and silica fume used, the cost and environmental impact of UHPC is considerably higher than conventional concrete. The use of industrial by-products as supplementary cementitious materials, in the case of recycled glass powder and fluid catalytic cracking catalyst residue (FCC), electric arc slag furnace (EASF), fly ash (FA), ground granulated blast slag furnace (GGBSF), rice husk ash (RHA) as partial substitution of cement and silica fume allows to create a more ecological and cost-efficient UHPC. Moreover, other products like limestone powder could be added to the mixture to reduce the final cost of UHPC and improve its rheology. For the 22 UHPC families with different binder composition tested, the design of the concrete mixtures was based on the goal of achieving mechanical and rheological properties with minimum amounts of cement, and a maximum amount of silica fume of 100 kg/m3, through a 3-factor Design of Experiments (DoE). The factors considered in this research were cement content in kg/m3 (factor A), water to binder ratio (factor B), and volume of superplasticizer (Factor C). Statistical tools such as Pareto plots, Principal Effect Plot, Stepwise Backward, Quadratic-order Regression, and Response Surface Methodology (RSM) were used to find the models for mechanical and rheological properties which included compressive strength at 1, 7, and 28-day, slump flow. Models for 28-day compressive strength and slump flow were the starting point for multi-objective optimization. The use of 590 kg/m3 of ASTM Type III cement, blended with micro limestone powder and recycled glass flour should be considered the most appropriate dosage to be employed in UHPC mixtures to reach a 28-day compressive strength over 150 MPa with a proper spread flow.

El hormigón de ultra alta resistencia (UHPC) es una innovación esencial en la investigación del hormigón de las últimas décadas. Sin embargo, debido a los altos contenidos de cemento y humo de sílice utilizados, el coste y el impacto medioambiental del UHPC es considerablemente mayor que el del hormigón convencional. El uso de subproductos industriales como materiales cementantes suplementarios, en el caso del polvo de vidrio reciclado y el residuo de catalizador de craqueo catalítico fluido (FCC), la escoria de horno de arco eléctrico (EASF), las cenizas volantes (FA), la escoria de alto horno granulada molida (GGBSF), la ceniza de cascarilla de arroz (RHA) como sustitución parcial del cemento y el humo de sílice permite crear un UHPC más ecológico y rentable. Además, otros productos como el polvo de piedra caliza podrían añadirse a la mezcla para reducir el coste final del UHPC y mejorar su reología. Para las 22 familias de UHPC con diferente composición de ligante ensayadas, el diseño de las mezclas de hormigón se basó en el objetivo de conseguir propiedades mecánicas y reológicas con cantidades mínimas de cemento, y una cantidad máxima de humo de sílice de 100 kg/m3, mediante un Diseño de Experimentos (DoE) de 3 factores. Los factores considerados en esta investigación fueron el contenido de cemento en kg/m3 (factor A), la relación agua/aglomerante (factor B) y el volumen de superplastificante (factor C). Se utilizaron herramientas estadísticas como los diagramas de Pareto, el diagrama de efectos principales, la regresión por pasos, la regresión de orden cuadrático y la metodología de superficie de respuesta (RSM) para encontrar los modelos de las propiedades mecánicas y reológicas que incluían la resistencia a la compresión a 1, 7 y 28 días y el flujo de asentamiento. Los modelos para la resistencia a la compresión a 28 días y el flujo de asentamiento fueron el punto de partida para la optimización multiobjetivo. El uso de 590 kg/m3 de cemento ASTM Tipo III, mezclado con polvo de microcaliza y harina de vidrio reciclado, debería considerarse la dosis más adecuada a emplear en las mezclas de UHPC para alcanzar una resistencia a la compresión a los 28 días superior a 150 MPa con un flujo de asentamiento adecuado.
Keywords: Hormigón - Aditivos; Concrete - Addititives; Resistencia de materiales; Strength of materials